The Drosophila cell corpse engulfment receptor Draper mediates glial clearance of severed axons. - MacDonald, J.M.; Beach, M.G.; Porpiglia, E.; Sheehan, A.E.; Watts, R.J.; Freeman, M.R. (Neuron, 2006)
Neuron-glia communication is central to all nervous system responses to trauma, yet neural injury signaling pathways remain poorly understood. Here we explore cellular and molecular aspects of neural injury signaling in Drosophila. We show that transected Drosophila axons undergo injury-induced degeneration that is morphologically similar to Wallerian degeneration in mammals and can be suppressed by the neuroprotective mouse Wlds protein. Axonal injury elicits potent morphological and molecular responses from Drosophila glia: glia upregulate expression of the engulfment receptor Draper, undergo dramatic changes in morphology, and rapidly recruit cellular processes toward severed axons. In draper mutants, glia fail to respond morphologically to axon injury, and severed axons are not cleared from the CNS. Thus Draper appears to act as a glial receptor for severed axon-derived molecular cues that drive recruitment of glial processes to injured axons for engulfment.